The Fate of Place : A Philosophical History - Casey, Edward S., 1939- (Book collections on Project MUSE., 2013)
In this imaginative and comprehensive study, Edward Casey, one of the most incisive interpreters of the Continental philosophical tradition, offers a philosophical history of the evolving conceptualizations of place and space in Western thought. Not merely a presentation of the ideas of other philosophers, The Fate of Place is acutely sensitive to silences, absences, and missed opportunities in the complex history of philosophical approaches to space and place. A central theme is the increasing neglect of place in favor of space from the seventh century A.D. onward, amounting to the vir.